Economic capital and financial risk management for financial services firms and conglomerates - Porteous Bruce T; Tapadar Pradip (Hampshire Palgrave Macmillan, 2006)
Topics covered include: the different types of risks that firms collect; risk governance issues; how stress testing can be used to measure risk; the provision of a clear and precise definition of economic capital; the different types of capital that are
Keywords: Capital management; Risk management